Effects of fasting and refeeding on the metabolic functions of the turtle Kinosternon scorpioides (Linnaeus, 1766) raised in captivity - Antonia S. Oliveira; Cinthia G. Candioto; Débora M.S. Santos; José G. Pereira; Alana L. Sousa; Célio R. Machado (Pesquisa Veterinária Brasileira, 2013)
The metabolic responses of adult and young freshwater Kinosternon scorpioides turtles raised in captivity were evaluated. Two experiments were performed: a) blood metabolite changes caused by food deprivation, and b) liver and muscle glycogen and total lipid differences after fasting and refeeding. Blood glucose concentration of young animals was susceptible to food deprivation. In both groups this metabolite decreased after 30 days of fasting. Feeding for 15 days did not recover blood glucose. Total seric proteins were not affected by food deprivation. Fasting decreased blood urea nitrogen and the highest difference was found around 30 days. Uric acid increased in young animals after 60 days of fasting. Triacylglicerol decreased after 15 days of fasting and refeeding for 15 days recovered the pre-fasting levels. Free fatty acid plasma tended to increase around 15 days of fasting. Liver glycogen decreased at day 15 of fasting, being stable thereafter while muscle glycogen decreased at a slower rate. Total liver lipid stabilized after 30 days and then decreased 70% after 60 days of fasting. Muscle lipids remained stable throughout fasting. It could be concluded that fasting of Kinosternon scorpioides led to metabolic adaptations similar to the one reported from reptiles and fish.